Fetal hemoglobin and alpha thalassemia modulate the phenotypic expression of HbSD‐Punjab. (19th November 2013) - Patel, D. K.; Purohit, P.; Dehury, S.; Das, P.; Dutta, A.; Meher, S.; Patel, S.; Bag, S.; Mashon, R. S.; Das, K.
Summary Introduction HbSD‐Punjab (HbSD) is a less common form of sickle cell disease (SCD) and discrimination between HbSD and HbSS is not possible on alkaline electrophoresis because the two variants overlap in the compound heterozygous state. There are only a few publications consisting mostly of case reports. Thus, the phenotypic expression of HbSD and its modifiers has not been studied. Methods We studied the phenotypic expression of 42 cases of HbSD (the largest number of subjects ever included in this kind of study) and compared them with 84 HbSS cases matched for age, sex, and caste. Further, we evaluated the influence of HbF concentration and alpha thalassemia on the phenotypic expressions of HbSD, namely the frequency of VOC and degree of hemolysis. Results The frequencies of VOC were similar in both the groups. The markers of hemolysis such as total bilirubin, unconjugated bilirubin, and LDH were higher where as HbF concentration was significantly low in HbSD. There was a negative correlation between HbF concentration and risk of VOC in the HbSD. The total hemoglobin level and hematocrit were significantly high, and the MCV and MCH were significantly low in HbSD with alpha thalassemia. Alpha thalassemia had no influence on the frequency of VOC and severity of hemolysis in HbSD. Conclusion HbF reduced the frequency of VOC but had no influence on the hemolytic markers in HbSD. HbSD with alpha thalassemia was associated with hypohromic and microcytic features of red blood cells.